Climate variability in the city of Trujillo-Perú - Bocanegra García, Carlos A. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
What has been happening in the city of Trujillo (Peru), is a notorious change in climatic variability that has occurred especially since the 1990s, attributable to the transformation of what was a desert coastal ecosystem by an impressive cover of vegetables (Chavimochic irrigation project). The methodology responds to a descriptive study that consisted of collecting secondary information on variables such as temperature, humidity, and precipitation. The conclusions corroborated the hypothesis that the transformation of the coastal desert ecosystem by artificial vegetation contributes to climatic variability in the city of Trujillo.